Coxsackie Virus Induced Graves’ Disease in an Immunocompetent Patient - Tang, DO, MPH, Wesley; Das, MD, Sulagna; Krudy, MD, Zoltán (International Journal of Innovative Research in Medical Science, 2021)
Enteroviruses, such as Coxsackie virus, have been implicated in the past as a pathogen associated with subacute thyroiditis, also known as de Quervain’s thyroiditis. Less commonly are viruses associated with autoimmune thyroid diseases such as Hashimoto’s thyroiditis and Graves’ disease. We present a case of a healthy 43 year old female who presented to the emergency department complaining of several months of weakness, nausea, loose bowel movements, anxiousness, and shortness of breath. Physical exam revealed tachycardia, tremors, and a non-tender thyroid gland to palpation. Skin exam showed a rash on the palms of her hands and soles of her feet bilaterally with dark papules, suggestive of Hand, foot, and mouth disease. Laboratory workup would reveal an undetectable thyroid stimulating hormone (TSH), and levels of T3 & T4 too high to quantify. Thyroid receptor antibodies would return as positive, diagnostic of Graves’ disease. Coxsackie virus (the causative agent of Hand, foot, and mouth disease) IgM titers also returned positive suggesting recent infection. Although the etiology of Graves’ disease is still not clear, this case report provides evidence that environmental triggers such as Coxsackie viral infection may be involved in its pathogenesis.